DEMOCRACY AS A PUBLIC IDEAL AND POLITICAL PRACTICE - Khrystyna Martsikhiv; Kateryna Seliverstova (Вісник Харківського національного університету імені В. Н. Каразіна: Серія "Питання політології", 2021)
The multifaceted democratic processes in modern political science are considered, which are reduced to a number of theoretical concepts related to defining the essence of the concepts of «democracy», people’s «freedom of speech», various concepts of democracy.